Pengaruh Suhu, Sistim Penyimpanan dan Lama Penyimpanan Terhadap Karakteristik Kimia Buah Tomat - Pattiruhu, Gysberth; Breemer, Rachel (Universitas Pattimura, 2024)
Tomato is one of the horticultural commodities that is highly perishable, thus requiring proper post-harvest handling to extend its shelf life. One approach to achieve this is by storing the tomatoes in suitable packaging and at an appropriate temperature. This study aims to evaluate the effect of storage temperature and storage systems on the chemical quality of tomatoes during storage. The experimental design used is a factorial completely randomized design, where the first factor is storage temperature at room temperature of 29˚C (A1) and low-temperature storage at 15˚C (A2), and the second factor is the storage system, consisting of closed control/stretch film (B1), modified packaging/stretch film with the addition of 6% O2 and 8% CO2 (B2), and open control/no packaging (B3), for durations of 4, 8, 12, and 16 days. The results showed that storage at 15˚C with modified packaging (A1B2) was able to maintain moisture content at 95.9%, vitamin C content at 3.67 mg/100g, reducing sugar at 2.43%, total acid at 10.6%, and calcium at 10.58% over a period of 16 days.